FUNCTIONING OF A NEUROMUSCULAR SYNAPSE IN CONDITIONS OF ALIMENTARY VITAMIN B1 DEFICIENCY - Romanenko, O.V.; Shepelev, S.E. (World of Medicine and Biology, 2013)
Influence of alimentary vitamin B1 (thiamine) deficiency on synaptic transmission in mice diaphragmatic muscle was investigated. In isolated phrenico-hemidiaphragmatic preparations obtained from animals gettings a thiamine-defficient diet, the amplitude of miniature end-plate potentials (mEPPs) and end-plate potentials (EPPs) on the 10th, 15th and 20th days of feeding and the quantal content of EPPs on the 20th day of feeding became significantly smaller than in preparations obtained from animals of control and pair-feed groups. The frequency of mEPPs, membrane potential of muscle fibers and the post-synaptic chemosensitivity to carbachol, the nicotinic acetylcholine receptors agonist, under influence of alimentary thiamine deficiency remained unchanged.
Keywords: vitamin B1; thiamine; neuromuscular transmission